Optimizing adrenal vein sampling in primary aldosteronism subtyping through LC–MS/MS and secretion ratios of aldosterone, 18-oxocortisol, and 18-hydroxycortisol - Chang, Yu-Ling; Chen, Guan-Yuan; Lee, Bo-Ching; Chen, Po-Ting; Liu, Kao-Lang; Chang, Chin-Chen; Weng, Te-I; Wu, Vin-Cent; Lin, Yen-Hung (Hypertension research, 2023)
Adrenal venous sampling (AVS) is the gold standard for identifying curable unilateral aldosterone excess in primary aldosteronism (PA). Studies have demonstrated the value of steroid profiling through liquid chromatography–tandem mass spectrometry (LC–MS/MS) in AVS interpretation. First, the performance of LC–MS/MS and immunoassay in assessing selectivity and lateralization was compared. Second, the utility of the proportion of individual steroids in adrenal veins in subtyping PA was analyzed. We enrolled 75 consecutive patients with PA who underwent AVS between 2020 and 2021. Fifteen adrenal steroids were analyzed in peripheral and adrenal veins through LC–MS/MS before and after adrenocorticotropic hormone (ACTH) stimulation. Through selectivity index that was based on cortisol and alternative steroids, LC–MS/MS rescued 45% and 66% of failed cases judged by immunoassay in unstimulated and stimulated AVS, respectively. LC–MS/MS identified more unilateral diseases than did immunoassay (76% vs. 45%, P < 0.05) and provided adrenalectomy opportunities to 69% of patients judged through immunoassay to have bilateral disease. The secretion ratios (individual steroid concentration/total steroid concentration) of aldosterone, 18-oxocortisol, and 18-hydroxycortisol were novel indicators for identifying unilateral PA. The 18-oxocortisol secretion ratio of ≥0.785‰ (sensitivity/specificity: 0.90/0.77) at pre-ACTH and aldosterone secretion ratio of ≤0.637‰ (sensitivity/specificity: 0.88/0.85) at post-ACTH enabled optimal accuracy for predicting ipsilateral and contralateral disease, respectively, in robust unilateral PA. LC–MS/MS improved the success rate of AVS and identified more unilateral diseases than immunoassay. The secretion ratios of steroids can be used to discriminate the broad PA spectrum.